AI in Regulatory Compliance: Revolutionizing Training with Fine-Tuned Language Models for Banking and Payment Systems - Gowda, Chandre (Journal of Global Economy, Business and Finance, 2025)
This article examines the use of fine tuned small Language Learning Models LLMs to develop AIdriven regulatory compliance training tailored for banking and payment systems. It discusses the integration of industry specific regulations, internal policies, and best practices into training modules, with a focus on personalized learning, interactive simulations, and real time updates. The proposed solution aims to improve training efficiency, ensure adherence to regulations, and deliver scalable, cost effective compliance training solutions. Additionally, the article addresses potential challenges, including data quality, model interpretability, and ethical considerations in AI deployment for regulatory training.